Integrating Bimetal Alloy into N‐Doped Carbon Nanotubes@Nanowires Superstructure for Zn‐Air Batteries. Issue 8 (24th March 2022) - Xu, Chen; Niu, Yanli; Gong, Shuaiqi; Liu, Xuan; Xu, Mingze; Liu, Tao; Chen, Zuofeng
Abstract: Exploring bifunctional oxygen electrocatalysts with low cost and high performance is critical to the development of rechargeable zinc‐air batteries, but it still remains a huge challenge. In this work, a "coordination construction‐pyrolysis/self‐catalyzed growth" approach was employed to fabricate branches@trunks‐like, N‐doped carbon nanotubes@nanowires superstructure with uniformly incorporated CoFe alloy nanoparticles (CoFe@CNTs‐NWs). The rational design of such hierarchical architecture could effectively enlarge the exposure of active sites, modulate their electronic structure, and assist the electron transfer and mass diffusion, thus benefiting both ORR and OER. The resultant CoFe@CNTs‐NWs displayed prominent bifunctional electrocatalytic activity and stability with a minimized oxygen overpotential of 0.71 V. When used as a cathode for zinc‐air batteries, it provided a high peak power density of 131 mW cm −2 and remarkable charge‐discharge stability for at least 400 cycles (130 h). This study presents a successful demonstration for optimizing the electrocatalytic performance by elaborate nanostructure and carbon matrix hybridization with simultaneous modulation of electronic structure, thus providing a new avenue to the rational design of transition metal‐based oxygen electrocatalysts. Abstract : Bifunctional oxygen electrocatalyst : A hierarchically structured material composed of uniform CoFe alloy nanoparticles incorporated in N‐doped carbon nanotubes‐grafted nanowires (CoFe@CNTs‐NWs) is constructed as a bifunctional oxygen electrocatalyst. It can be used as an efficient air cathode in the rechargeable Zn‐air batteries, exhibiting high power density and excellent cycling stability.